2020
DOI: 10.1080/10669817.2020.1821327
|View full text |Cite
|
Sign up to set email alerts
|

Embedding pain neuroscience education in the physical therapy management of patients with chronic plantar fasciitis: a prospective case series

Abstract: Objectives: The purpose of this case series was to describe the effects of a biopsychosocial approach that embeds pain neuroscience education (PNE) within physical therapy for improving foot and ankle function, pain, and psychosocial factors in patients with chronic plantar fasciitis. Methods: Seven female patients (mean [SD] age = 49.0 [11.4] years) receiving physical therapy for chronic plantar fasciitis were enrolled. Along with formal physical therapy, patients received six 15-minute PNE sessions. Knowledg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…When the metatarsophalangeal joint is flexion, the plantar fascia is pulled to increase the arch angle of the foot. Human long-term walking, standing, running, and jumping and other movements lead to strain at the starting point of plantar aponeurosis and then degeneration, resulting in tearing, degeneration, chronic fibrous tissue inflammation, edema, and thickening of plantar fascia [ 16 ]. Therefore, PF is a syndrome of coexistence and interaction of inflammation and degeneration [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the metatarsophalangeal joint is flexion, the plantar fascia is pulled to increase the arch angle of the foot. Human long-term walking, standing, running, and jumping and other movements lead to strain at the starting point of plantar aponeurosis and then degeneration, resulting in tearing, degeneration, chronic fibrous tissue inflammation, edema, and thickening of plantar fascia [ 16 ]. Therefore, PF is a syndrome of coexistence and interaction of inflammation and degeneration [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Human long-term walking, standing, running, and jumping and other movements lead to strain at the starting point of plantar aponeurosis and then degeneration, resulting in tearing, degeneration, chronic fibrous tissue inflammation, edema, and thickening of plantar fascia [ 16 ]. Therefore, PF is a syndrome of coexistence and interaction of inflammation and degeneration [ 16 ]. PF is a kind of chronic aseptic inflammation, and the age of onset is mostly between 40 and 70 years old.…”
Section: Discussionmentioning
confidence: 99%
“…Based on this information, pain and pain-related behaviors should be considered the results of interactions between biological, psychological, social, and contextual factors. Pain neuroscience education (PNE) is an example of a biopsychosocial approach in the field of physical therapy [5,6]. PNE is a top-down educational therapy that changes patients' beliefs based on a neurophysiological understanding of pain [7,8], and focuses on pain experience and cognition of chronic pain [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…In a meta-analysis of the effects of PNE on kinesiophobia in patients with chronic pain, it was reported that a combined intervention of manual therapy and exercise therapy was effective in improving chronic pain and kinesiophobia [5,6,11]. Similarly, soft-tissue mobilization (STM) in CNLBP has been reported as a manual therapy that could help avoid short-term pain, disability, and fear [11].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to having negative effects on physical and social activities, it causes losses in terms of financial resources and workforce (23). The restriction of physical activities by plantar heel pain and the fact that individuals put barriers both socially and psychologically due to this problem negatively affect health-related quality of life (24,25). Many previous studies have shown that plantar heel pain has adverse effects on various aspects of the individual's life, including ADL, quality of life related to the foot and ankle, and functions in sports and recreational activities (26).…”
Section: Discussionmentioning
confidence: 99%